2021
DOI: 10.1101/2021.06.17.21259092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Domain Generalization and Adaptation on Improving Model Robustness to Temporal Dataset Shift in Clinical Medicine

Abstract: Importance: Temporal dataset shift associated with changes in healthcare over time is a barrier to deploying machine learning-based clinical decision support systems. Algorithms that learn robust models by estimating invariant properties across time periods for domain generalization (DG) and unsupervised domain adaptation (UDA) might be suitable to proactively mitigate dataset shift. Objective: To characterize the impact of temporal dataset shift on clinical prediction models and benchmark DG and UDA algorith… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Our descriptions of temporal dataset shift on model performance in MIMIC-IV were consistent with previously seen results. 20 There have been few published reports demonstrating methods that can proactively improve model robustness to temporal dataset shift in clinical medicine, 2 21 and recent attempts using domain generalization and unsupervised adaptation were unsuccessful. 20 Previous work exploring causal and noncausal feature selection on medical datasets found that while causal feature selection could mitigate nontemporal covariate shift to an extent, it generally did not outperform regularization-based feature selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our descriptions of temporal dataset shift on model performance in MIMIC-IV were consistent with previously seen results. 20 There have been few published reports demonstrating methods that can proactively improve model robustness to temporal dataset shift in clinical medicine, 2 21 and recent attempts using domain generalization and unsupervised adaptation were unsuccessful. 20 Previous work exploring causal and noncausal feature selection on medical datasets found that while causal feature selection could mitigate nontemporal covariate shift to an extent, it generally did not outperform regularization-based feature selection.…”
Section: Discussionmentioning
confidence: 99%
“…20 There have been few published reports demonstrating methods that can proactively improve model robustness to temporal dataset shift in clinical medicine, 2 21 and recent attempts using domain generalization and unsupervised adaptation were unsuccessful. 20 Previous work exploring causal and noncausal feature selection on medical datasets found that while causal feature selection could mitigate nontemporal covariate shift to an extent, it generally did not outperform regularization-based feature selection. 22 While one study showed that causal feature selection outperformed other feature selection methods to mitigate temporal dataset shift, the setting was stock market prediction, a nonclinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…As such domain shifts lead to a drop in performance, there exist different approaches to handle that problem, e.g. data augmentation Yao et al [2022], domain generalization Wang et al [2021] and domain adaptation (DA) Wang and Deng [2018], Guo et al [2021]. Domain generalization and DA are closely related.…”
Section: Introductionmentioning
confidence: 99%